2013
DOI: 10.3989/scimar.03757.26a
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive output traits of the simultaneous hermaphrodite <I>Serranus scriba</I> in the western Mediterranean

Abstract: SUMMARY:We studied multiple individual parameters that affect the reproductive output in the painted comber Serranus scriba, a simultaneous hermaphroditic fish that is widely exploited by recreational fishing in temperate marine coastal regions. Batch fecundity was significantly affected by maternal size, but was not related to maternal age or condition. However, egg quality as estimated by egg dry weight was significantly influenced by the interaction effect of maternal size and age. An empirical assessment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
(62 reference statements)
1
0
0
Order By: Relevance
“…This relative low production might be related to the spawning frequency of this species that must be high to compensate the low number of hydrated oocytes produced. However, the values of RBF found in this study were close to those reported by Alós et al (2013) and Neves et al (2014) Fecundity is also affected by the fish size, weight and condition, being the key parameters to assess fecundity at the population level (KJESBU et al, 1991;. Thus, the RBF was negatively affected by all factors measured, revealing that the smaller specimens with a better condition produce more hydrated oocytes per gram of body.…”
Section: Reproductive Traits Of the Simultaneous Hermaphrodite Dipletsupporting
confidence: 85%
“…This relative low production might be related to the spawning frequency of this species that must be high to compensate the low number of hydrated oocytes produced. However, the values of RBF found in this study were close to those reported by Alós et al (2013) and Neves et al (2014) Fecundity is also affected by the fish size, weight and condition, being the key parameters to assess fecundity at the population level (KJESBU et al, 1991;. Thus, the RBF was negatively affected by all factors measured, revealing that the smaller specimens with a better condition produce more hydrated oocytes per gram of body.…”
Section: Reproductive Traits Of the Simultaneous Hermaphrodite Dipletsupporting
confidence: 85%